Pakistan : Staff Report for the 2011 Article IV Consultation and Proposal for Post-Program Monitoring. (IMF Staff Country Reports; Country Report ;, 2012)
Pakistan has implemented some reforms, including improvements in tax administration, removal of some tax exemptions, and the introduction of an interest rate corridor. The macroeconomic policies are overly expansionary and fundamental reforms to resolve the economy's structural problems are not being tackled well. There is broad concurrence between the authorities and the mission on policy priorities, namely, tighter fiscal policy, a less accommodative monetary policy stance, and structural reforms. The government recognizes that the economy has performed well below its potential and requires an annual average rate of 7 percent to absorb youth labor growth.